Digital printing of textiles - Ujiie, H. (Hitoshi) (Woodhead publishing in textiles., 2006)
At present the textile industry produces the majority of its 34 billion square yards of printed textile fabric by screen printing. However as we move into the digital age developments in digital printing of paper are being adapted more and more for the textile market. Inkjet textile printing is growing while growth in analog textile printing remains stagnant. As digital print technologies improve offering faster production and larger cost-effective print runs, digital printing will grow to become the technology that provides the majority of the world's printed textiles. This comprehensive introduction to the subject is broken into five sections. After two introductory chapters, it goes on to look in a number of detailed chapters at printer and print head technologies. The next section examines the printer software required for successful colour design and management. The digital printing colouration process is explored next, with chapters on substrate preparation, pigmented ink, aqueous inkjet ink, pre-treatment and printing on cationized cotton with reactive inks. The book is concluded with three chapters on the design and business aspect of digital printing. Digital printing of textiles contains fundamental technical explanations along with recent research, and is an invaluable guide for product developers, retailers, designers and academic researchers. Provides coverage of all the current developments in digital textile printingCovers important areas such as printer and print head technologies, printer software, digital printing colouration and design and business for digital printing.